Predicting intracerebral hemorrhage after endovascular therapy for anterior circulation strokes using CT-ASPECT, CTP-ASPECT and DWI-ASPECT: Protocol for a systematic review. - Vincent Brissette; Chirayu Bhatt; Brian Dewar; Risa Shorr; Jordi Pardo; Robert Fahed; Michel Shamy; Dar Dowlatshahi (PLoS ONE)
Introduction Over the last decade, there have been significant advances in treatments for anterior ischemic stroke, most notably endovascular thrombectomy (EVT). Despite the success of EVT on overall outcomes, intracerebral hemorrhage (ICH) is an important post-procedure complication, often associated with mortality and disability. Hence, predicting the risk of ICH can inform EVT decision making. The ASPECT score is used globally to predict patients' prognosis post-reperfusion therapy. Our objective is to perform a systematic review to collect and synthesize data on the association between ASPECT scores on CT, CTP and DWI-MRI (CT-ASPECT, CTP-ASPECT, and DWI-ASPECT) and the risk of symptomatic ICH after EVT for anterior circulation strokes. Methods and analysis We will conduct a broad search of various electronic databases (MEDLINE, EMBASE, CINAHL, PsycINFO, Web of Science, and the Cochrane Database of Systematic Reviews) to identify studies published after January 1st, 2012 (commonly accepted as the beginning of the modern EVT era based on availability of stent-retrievers). Two independent reviewers will screen and include studies evaluating associations between symptomatic ICH after thrombectomy and baseline CT-ASPECT, CTP-ASPECT and DWI-ASPECT scores. Data will be extracted to quantify the risk of sICH after EVT based on the ASPECT scoring. Trial registration PROSPERO registration number: CRD42023459860.